Traditional versus iPad-mediated handwriting instruction in early learners. Issue 2 (2nd April 2016) - Wells, Kevin E.; Sulak, Tracey N.; Saxon, Terrill F.; Howell, Leanne L.
ABSTRACT: There has been a drastic increase in the use of technology in the classroom over the past 20 years. As computers and tablets permeate our schools, their presence is oftentimes seen as a cure to whatever problems may exist. While the promise of technology has held true within some domains, little has been done to examine its efficacy in some areas. The literature remains largely silent about the use of technology as a handwriting intervention in struggling learners. This study compared handwriting practice performed on iPads to handwriting practice performed through traditional means to determine the extent to which iPad-mediated handwriting practice transfers to traditional assessments. Twelve kindergarten and first-grade students from an urban public elementary school in central Texas participated in this small-scale study. The results indicate that traditional methods, while similar, were superior in terms of letter formation and letter orientation to iPad-mediated practice. Likewise, letter recognition increased for those using traditional handwriting methods but stayed stable for the iPad-mediated group. Similarly, iPad-mediated letter production was increased more so than with traditional methods. This study demonstrates a real world example of what an intervention looks like in a public school setting.